A FEMINIST CRITIQUE OF CHACOAN ARCHAEOLOGY: COMMENT ON HEITMAN'S (2016) FEMINIST SCIENCE AND CHACOAN ARCHAEOLOGY. Issue 3 (1st August 2017) - Ware, John
Abstract : Heitman's (2016 ) feminist critique of Chacoan archaeology omits consideration of matrilineal descent theory. Abstract : En su crítica feminista de la arqueología del Cañon del Chaco, Heitman (2016) omite una consideración teorética del matrilinaje.